Strategi manajemen inovasi produk dalam meningkatkan daya saing bank pembiayaan rakyat syariah (BPRS) di era digital - Dhofiri, Ahmad Hamdan (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the product innovation management strategies implemented by Islamic Rural Banks (BPRS) to enhance competitiveness in the digital era. Increasing competition among financial institutions requires BPRS to innovate in order to meet customer needs quickly, efficiently, and in accordance with Sharia principles. This research employs a descriptive qualitative method through literature analysis and secondary data obtained from various academic sources and industry reports. The results show that effective product innovation strategies in BPRS include the digitalization of financing services, the development of Sharia-based financial technology (Islamic fintech) products, and the enhancement of digital literacy among employees and customers. By implementing these strategies, BPRS can strengthen institutional image, expand market segments, and increase public trust in Islamic banking.